Impact of Albuminuria and Renal Dysfunction on the Anemia-Improving Effect of SGLT2 Inhibitors in Patients With Type 2 Diabetes: A Real-World Observational Study - Ayami Kajiwara-Morita; Kentaro Oniki; Akira Yoshida; Noboru Kurinami; Tomoko Suzuki; Fumio Miyamoto; Kunio Hieshima; Seigo Sugiyama; Keizo Kajiwara; Katsunori Jinnouchi; Junji Saruwatari; Hideaki Jinnouchi (Journal of Diabetes Research, 2025)
Conclusions: Our findings indicate that severely increased albuminuria attenuates the anemia-improving effect of SGLT2 inhibitors for at least 3 months after their administration.